(untitled) (Global Journal of Medical Research, 2022)
This study aims to find that there is any association between Periodontal diseases with factors like diabetes, depression, blood pressure, age, gender, alcohol, smoking, education level, and obesity. For this study data were taken from National Health and Nutrition Examination Survey (NHANES). From this data various variables are taken and test in SAS 9.4 software for analysis. This study is done on a 3737 sample in which 734 people reported having gum/periodontal disease. Logistic regression analysis was performed with variables. We found a significant association between diabetes, depression, age, smoking, and obesity to have periodontal disease.